Interfacial water engineering for enhanced pure water electrolysis - Adam Gopal Ramu; Dongjin Choi (Scientific Reports)
Abstract We report the development of a novel self-organized water (SOW) electrolyzer using a plasma electrolytic oxidation (PEO)-treated platinum-titanium (PEO-Pt/Ti) heterostructure electrode, demonstrating exceptional performance in the hydrogen evolution reaction (HER). Hydrophilic materials like Nafion are critical for forming interfacial water zones with distinct properties compared to bulk water. We investigated the effects of infrared (IR) light on the negatively charged SOW and positively charged protonated water (PW) near Nafion surfaces. Mid-IR irradiation for 13 min significantly expanded the SOW, enhancing its ability to facilitate the dissociation of interfacial water into hydroxide ions (OH⁻) and protons (H⁺), thus driving efficient water splitting. The PEO-Pt/Ti electrode, synergized with optimized SOW, modulates electronic states, increases active surface area, improves conductivity, and lowers activation energy barriers. This enables current densities of 100 mA cm⁻² at 3.1 V and superior H₂ production at 3.5 V, with stable operation exceeding 25 h. These findings highlight the system’s durability, efficiency, and cost-effectiveness. By integrating advanced electrode engineering with SOW systems, this work introduces a scalable strategy for sustainable hydrogen production, addressing key challenges in clean energy generation and advancing renewable energy technologies.